Developing a performance measurement framework to benchmark the South African wine supply chain with a focus on the packaged export supply chain segment - Roos, Tielman (Stellenbosch : Stellenbosch University, 2016)
Stellenbosch University. Faculty of Engineering. Dept. of Process Engineering.